STRATEGI MEMAHAMI KATA-KATA SULIT DALAM MEMBACA TEKS BERBAHASA INGGRIS - Siti Nurhayati (Tatar Pasundan : Jurnal Diklat Keagamaan, 2018)
The purpose of writing this article is to describe the easy way to understand difficult words in reading scientific texts in English. We often find difficult words, which hinder understanding of the contents of English-language reading. In fact, we are often lazy to continue reading, and are very time consuming when searching for the meaning of words in a dictionary. If only one or two words are found it doesn't matter. However, if more than ten difficult words will interfere and hinder understanding of the contents of the reading, and will depend on the dictionary. For that there are several steps we can take to avoid obstacles in understanding the English text as a whole. For that reason, there is no need to worry if finding difficult words in a text, through the context of the sentence can help guess the exact meaning of the word.Key words: Difficultwords, Strategy, and English Text